Novel phthalocyanines bearing both quaternizable and bulky substituents - KOCA, ATIF (ELSEVIER SCI LTD, 2008)
A new phthalonitrile derivative bearing dimethylaminoethylsulfanyl- and diethoxymalonyl-substituents at peripheral positions has been synthesized. Cyclotetramerization of this dinitrile in hexanol gave the desired cobalt(II) and zinc(II) phthalocyanines (4 and 5) with dinnethylarninoethylsulfanyl and dihexoxymalonyl groups on periphery. Four dimethylarninoethyl groups of the former were quaternized to yield a water-soluble cobalt(II) phthalocyanine. Electrochemical redox properties of these phthalocyanines were investigated by cyclic voltarnmetry and applied chronocoulometry techniques. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: phthalocyanine; phthalonitrile; water-soluble; zinc; cobalt; cyclic voltammetry; PHOTODYNAMIC THERAPY; PHOTOSENSITIZERS; MOIETIES; BEHAVIOR